PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS V SD SAWAH BESAR 01 - Didi Prabowo; Henry Januar Saputra; Filia Prima Atharina (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
This research aims to examine the effect of project-based learning through biopore learning models on the learning outcomes of elementary school students in grade V, to examine the effect of project-based learning through biopori learning outcomes on learning outcomes of elementary school students. This study used a pre-experimental design in the form of a one-group pretest-posttestdesign. The study population was all students in grade V SD Negeri Sawah Besar 01 Semarang, totaling 40 children. The sample of all students in grade V SD Negeri Sawah Besar 01 Semarang, totaling 40 students, namely 23 male students and 17 female students obtained by simple random sampling. The independent variable is the project based learning model, while the dependent variable is the learning outcome. Data were collected by interview, test, and documentation. The research hypothesis was tested with Liliefors using the Microsoft Office Excel program. The conclusions of the research results are: There is a positive influence on the learning model of project based learning on the learning outcomes of students in class V SD Sawah Besar 01.